2021
DOI: 10.1021/acs.organomet.1c00237
|View full text |Cite
|
Sign up to set email alerts
|

Role of the X Coligands in Cyclometalated [Ni(Phbpy)X] Complexes (HPhbpy = 6-Phenyl-2,2′-bipyridine)

Abstract: The coligand X was varied in the organonickel complexes [Ni(Phbpy)X] (X = F, Cl, Br, I, C 6 F 5 ) carrying the anionic tridentate C ∧ N ∧ N ligand 6-(phen-2-ide)-2,2′-bipyridine (Phbpy − ) to study its effect on electronic structures of these complexes and their activity in Negishi-like C−C cross-coupling catalysis. The complexes were synthesized from the precursor [Ni(COD) 2 ] (COD = 1,5-cyclooctadiene) by chelate-assisted oxidative addition into the phenyl C−X bond of the protoligand 6-(2-halidophenyl)-2,2′-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 62 publications
1
20
0
Order By: Relevance
“…Related Ni­(I)–bpy halide complexes have been prepared by alternate methods, including pulse radiolysis, electrolysis, and independent synthesis. Importantly, these compounds have demonstrated potency for the activation of aryl halide substrates. Following the work by Vicic and co-workers on Ni­(I)–terpyridine complexes, Bird and MacMillan and co-workers reported a nickel­(I)­(4,4′-di- tert -butyl bipyridine)­bromide complex (Ni­(I)­( t ‑Bu bpy)­Br) that exhibited rapid reactivity toward aryl iodides with second-order rate constants of ∼10 4 M –1 s –1 . The activation of C­(sp 2 )–Br substrates was demonstrated by Doyle and co-workers using a nickel­(I)­(diethyl-2,2′-bipyridine-4,4′-dicarboxylate)­chloride complex, Ni­(I)­( EtOOC bpy)­Cl.…”
Section: Introductionmentioning
confidence: 97%
“…Related Ni­(I)–bpy halide complexes have been prepared by alternate methods, including pulse radiolysis, electrolysis, and independent synthesis. Importantly, these compounds have demonstrated potency for the activation of aryl halide substrates. Following the work by Vicic and co-workers on Ni­(I)–terpyridine complexes, Bird and MacMillan and co-workers reported a nickel­(I)­(4,4′-di- tert -butyl bipyridine)­bromide complex (Ni­(I)­( t ‑Bu bpy)­Br) that exhibited rapid reactivity toward aryl iodides with second-order rate constants of ∼10 4 M –1 s –1 . The activation of C­(sp 2 )–Br substrates was demonstrated by Doyle and co-workers using a nickel­(I)­(diethyl-2,2′-bipyridine-4,4′-dicarboxylate)­chloride complex, Ni­(I)­( EtOOC bpy)­Cl.…”
Section: Introductionmentioning
confidence: 97%
“…Hörner and Klein explored the role of the coligand-X (X = F, Cl, Br, I, and C 6 F 5 ) in determining the electronic features of cyclometalated Ni complexes, [Ni(Phbpy)X] (Phbpy = 6-phenyl-2,2′-bipyridine), and studied their effect in Negishi coupling. 27 The catalytic activity of these Ni complexes in Negishi coupling suggested that all the complexes were effective catalysts but did not exhibit any remarkable differences in moving from Ni-F to Ni-I. However, they observed an effect of the coligand on product selectivity in the order I ≫ Br > Cl ≈ F. In addition to this, varying the substituent R on the ligand influenced the activity of the complex [Ni(R-Phbpy)Br].…”
Section: Classificationmentioning
confidence: 99%
“…We became interested in hydrido Ni­(II)­complexes in the course of the comparison of the two cyclometalating ligands – Phbpy (HPhbpy = 6-phenyl-2,2′-bipyridine) and PyPh­( − )­Py (Py­(HPh)­Py = 2,6-di-2-pyridyl-benzene) (Chart ). , The former provides a C ∧ N ∧ N coordination to a square planar Ni­(II) center in complexes of the type [Ni­(Phbpy)­(X)] and some derivatives (X = Br, CF 3 , CH 3 ) and R­(Ph)­(R′bpy) have been explored recently for their optical and electrochemical properties. The X = Br complexes are rather stable in contrast to the corresponding CF 3 and CH 3 derivatives exhibiting facile reductive elimination (RE) that yields F 3 C–Phbpy and H 3 C–Phbpy due the cis -orientation of the two carbanionic groups .…”
Section: Introductionmentioning
confidence: 99%
“…We became interested in hydrido Ni­(II)­complexes in the course of the comparison of the two cyclometalating ligands – Phbpy (HPhbpy = 6-phenyl-2,2′-bipyridine) and PyPh­( − )­Py (Py­(HPh)­Py = 2,6-di-2-pyridyl-benzene) (Chart ). , The former provides a C ∧ N ∧ N coordination to a square planar Ni­(II) center in complexes of the type [Ni­(Phbpy)­(X)] and some derivatives (X = Br, CF 3 , CH 3 ) and R­(Ph)­(R′bpy) have been explored recently for their optical and electrochemical properties. The X = Br complexes are rather stable in contrast to the corresponding CF 3 and CH 3 derivatives exhibiting facile reductive elimination (RE) that yields F 3 C–Phbpy and H 3 C–Phbpy due the cis -orientation of the two carbanionic groups . In the recently studied trans -C-X configured [Ni­(PyPhPy)­(X)] (X = Cl, Br, I) complexes containing a N ∧ C ∧ N cyclometalated ligand, the trans -influence of the strongly σ-donating carbanionic phen-2-ide group (Ph – ) labilizes markedly the Ni–X bond. , This bonding situation might suppress intramolecular concerted RE reactivity for carbanionic coligands as R = alkyl, aryl, or H but rather allows for intermolecular R or H transfer or radical eliminations.…”
Section: Introductionmentioning
confidence: 99%